Path Planning and Funnel Control for Wheeled Mobile Robot Based on Signal Temporal Logic - TIAN Chang; ZHU Huajie; YANG Yan; SHI Zhongjiao; LIU Zhijie (Kongzhi Yu Xinxi Jishu)
Temporal logic can ensure the accurate description and execution of task specifications by providing a rich specification language. This paper uses relevant robust semantics to consider continuous-time systems under signal temporal logic specification fragments and uses a funnel-based feedback control law to realize collaborative design of path planning and control of wheeled mobile robot. This design not only introduces a strict and effective formal verification method, but also provides a computationally-efficient funnel-based feedback control law. Firstly, it describes the mission by signal temporal logic. Then, it transforms the description into robust formula. Finally, using the funnel-based feedback control law, it makes the robust semantics of the robust formula maximum to realize the collaborative design of path planning and control. Simulation is based on the wheeled mobile robot kinematics model, and the results show that the collaborative design method proposed in this paper is effective. When the specification is physically met, the system can achieve the goal with user-defined robustness. When the specification is not satisfied, the minimum violation solution can be found. The proposed path planning and funnel control algorithm can realize the collaborative design of the path planning and control of the wheeled mobile robot, which effectively improve computing efficiency and simplify computational complexity. The study can expand the application range of signal temporal logic in mobile robot path planning, and increase the system robustness.